Answer:
24.58
Step-by-step explanation:
Answer:
X >>>>> Y
–1 >>>> 16
0 >>>>> 8
1 >>>>> 4
2 >>>>> 2
3 >>>>> 1
Step-by-step explanation:
From the question given above,
y = 8 × (½)ˣ
When x = –1, y =?
y = 8 × (½)ˣ
y = 8 × (½)¯¹
y = 8 × 2
y = 16
When x = 1, y =?
y = 8 × (½)ˣ
y = 8 × (½)¹
y = 8 × ½
y = 4
When x = 2, y =?
y = 8 × (½)ˣ
y = 8 × (½)²
y = 8 × ¼
y = 2
When x = 3, y =?
y = 8 × (½)ˣ
y = 8 × (½)³
y = 8 × ⅛
y = 1
SUMMARY:
X >>>>> Y
–1 >>>> 16
0 >>>>> 8
1 >>>>> 4
2 >>>>> 2
3 >>>>> 1
Answer: do the math, 39x
Step-by-step explanation:2+4=6 times 7=42-19=23+7=30+9=39x
Answer:
( -0.5 , 6.5 )
Step-by-step explanation:
Answer:
its sophisticated but answer is 3
Step-by-step explanation:
you have to dive deep into it and research